The effect of modified jackfruit(artocarpus heteropyllus lam.)seed starch on the propertiesof poly (lactic acid) (pla) - Nur Amira Sahirah Binti Abdullah (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
The effect of the modified jackfruit seed starch on the properties of PLA were investigated. The blend systems were prepared by melt blending method and compression molding. There are total of three blend system studied; poly (lactic acid) blend with native jackfruit seed starch (PLA/JF), poly (lactic acid) blend with silanized jackfruit seed starch(PLA/JFS) and poly (lactic acid) blend with thermoplastic jackfruit seed starch (PLA/JFT). The main purpose of this work is to study the effect of modifications of jackfruit seed starch when blended with poly (lactic acid) (PLA). There are two type of modifications that has been done which are silane coupling agent and modification with glycerol that to convert particulate starch to the thermoplastic like. The success of the modification was analyzed using FTIR.The physicochemical properties and thermal stability of the native and modified jackfruit seed starch blends with PLA were comparatively investigated by using tensile test and thermogravimetric analysis (TGA). For the all blends system as the filler loading increases, the tensile strength decreaseswhile the Youngs modulus, the JF and JFS shows the significant improvement. The elongation at break of the JFT based systems increasing as the JFT loading increasing and gives the ductile behavior to the blend. The modification of the starch with silane coupling agent gives better interfacial adhesion between starch and PLA while the glycerol gives the ductility and characteristic to the PLA matrix. The thermal stability of the PLA/modified starch was improved as compared with PLA/JF. For the soil burial test, the samples show that the bacterial colonies started to formed and formation of the crack occurred after 30 days.